The Effect of Standard Hospital Care on Chemotherapy Induced Nausea and Vomiting (CINV), Chemotherapy Induced Peripheral Neuropathy (CIPN) and Anxiety in Breast Cancer Patients With Chemotherapy in Jember, Indonesia - Mu'awanah, Siti; Ahsan, Ahsan; Windarwati, Heni Dwi (Jurnal Health Sains, 2023)
Breast cancer has a large number of new cases and deaths in the world and Indonesia. Chemotherapy is one of the treatments chosen to treat breast cancer patients. Physical side effects can include Chemotherapy-induced Induced Nausea and Vomiting (CINV), Chemotherapy-induced Induced Peripheral Neuropathy (CIPN) and anxiety. Standard hospital care is care in which nursing actions are in accordance with the Standard Operating Procedure (SOP) that the hospital has established for each existing service. The research method used was quasi-experimental (quasi-experiment), which was carried out with an unequal control group design. The pre-test was carried out during chemotherapy when the researcher met the respondent, and the post-test was carried out during the respondent's following chemotherapy schedule. The population in this study were breast cancer patients undergoing chemotherapy at the chemotherapy clinic at RSD, Dr. Soebandi Jember and Rumkit Kindergarten. III Baladhika Husada Jember . The sampling method used was simple random sampling with a minimum sample size of 60 people. The results of the Paired Samples Test can be concluded that standard treatment in hospitals does not affect the level of Chemotherapy Induced Nausea and Vomiting (CINV) but does influence the incidence rate of chemotherapy-induced peripheral neuropathy (CIPN) and the level of anxiety in breast cancer patients with chemotherapy.